Influences of infill percentage, bed temperature and outer perimeters on elongation of 3D printed nylon 6. (2022) - Kumar, Ranvijay; Ranjan, Nishant
Abstract: The present study highlights the influences of input process variables on the elongation property of nylon 6 thermoplastic prototypes prepared by the fused filament fabrication (FFF) process. In this study, the FFF process has been conducted by varying the input process variables such as; infill percentage (70, 85 and 100%), bed temperature (50, 60 and 70 °C) and outer perimeters (4, 5 and 6 perimeters). The parts of nylon 6 thermoplastic have been prepared as per the dimension of ASTM D 638 type IV. The prepared parts have been subjected to universal tensile testing (UTT) for the investigations of elongation as the outcome of varying input process parameters. The elongation properties have been optimized by conducting the analysis based upon the signal to noise (SN) ratio of the elongation property.